2023
DOI: 10.1007/s11846-023-00694-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards data-driven decision making: the role of analytical culture and centralization efforts

Ágnes Szukits,
Péter Móricz

Abstract: The surge in data-related investments has drawn the attention of both managers and academia to the question of whether and how this (re)shapes decision making routines. Drawing on the information processing theory of the organization and the agency theory, this paper addresses how putting a strategic emphasis on business analytics supports an analytical decision making culture that makes enhanced use of data in each phase of the decision making process, along with a potential change in authorities resulting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…In the context of existing literature, the findings of this study are consistent with the results of previous studies that highlight the importance of Big Data in creating competitive advantage and driving innovation. Several previous studies have also found that organisations that are able to effectively adopt a data-driven culture tend to be more successful in leveraging Big Data for better decision-making and identifying new opportunities for growth (Brewis et al, 2023;Chatterjee et al, 2023Chatterjee et al, , 2024Martínez-Peláez et al, 2023;Schlegel et al, 2023;Szukits & Móricz, 2023;Tran, 2017;Wei, 2023).…”
Section: The Importance Of Big Data As An Innovation In Decision-maki...mentioning
confidence: 97%
See 1 more Smart Citation
“…In the context of existing literature, the findings of this study are consistent with the results of previous studies that highlight the importance of Big Data in creating competitive advantage and driving innovation. Several previous studies have also found that organisations that are able to effectively adopt a data-driven culture tend to be more successful in leveraging Big Data for better decision-making and identifying new opportunities for growth (Brewis et al, 2023;Chatterjee et al, 2023Chatterjee et al, , 2024Martínez-Peláez et al, 2023;Schlegel et al, 2023;Szukits & Móricz, 2023;Tran, 2017;Wei, 2023).…”
Section: The Importance Of Big Data As An Innovation In Decision-maki...mentioning
confidence: 97%
“…The research also highlights the importance of developing a data-oriented organisational culture to support the application of big data in decision-making strategies and the achievement of competitive advantage with research support (Aseeri & Kang, 2022;Bozkus, 2024;Farida & Setiawan, 2022;Lunde et al, 2019;Shabbir & Gardezi, 2020;Szukits & Móricz, 2023;Yousuf, 2020). This requires full support from upper management to promote the use of big data in decision-making, as well as investment in training and development of employees to improve their data literacy and analytical skills.…”
Section: The Strategic Role Of Big Data In Creating Competitive Advan...mentioning
confidence: 99%
“…In the Fourth Industrial Revolution, the decision-making process has become data-based and contributes to reshaping industries [12,13]. In this context, assessing the health of the transformer and the remaining lifespan for its efficient operation depends on how the data of periodic tests or tests accompanying faults [14,15].…”
Section: Introductionmentioning
confidence: 99%